Fact: The Form of Participation Does Matter—A Rebuttal to Leana, Locke, and Schweiger - Cotton, John L.; Vollrath, David A.; Lengnick-Hall, Mark L.; Froggatt, Kirk L. (Academy of Management Review, 1990)
In responding to the critique by Leana, Locke, and Schweiger (1990) of our review, we identify points of confusion and misunderstanding, disagreements in judgment, and comments with which we agree. Our original conclusion stands: The form of participation influences the effectiveness of that participation. Leana et al. simply show that excluding certain forms of participation from consideration yields results that are considerably different. We discuss how their critique demonstrates the importance of clarity, as well as judgment decisions, in research reviews.